The Influence Of Perceived Quality, Brand Trust, And Customer Satisfaction On Customer Loyalty At PT. Sinar Sakti Sampoerna - Vanessa Amalia; Tri Lestira Putri Warganegara (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to examine the effect of Perceived Quality, Brand Trust, and Customer satisfaction on Customer loyalty among customers of PT. Sinar Sakti Sampoerna. Intense competition in the logistics service industry requires companies not only to attract customers but also to maintain their loyalty. This research employs a quantitative approach with an associative research design and an ex-post facto method to analyze the influence of Perceived Quality, Brand Trust, and Customer satisfaction on Customer loyalty. The research population consists of 3,162 customers, with a sample of 97 respondents. Data were collected through Likert-scale questionnaires and documentation, then analyzed using multiple linear regression, instrument validity and reliability tests, descriptive statistics, normality and homogeneity tests, as well as hypothesis testing using independent t-tests and ANOVA. The results indicate that Perceived Quality, Brand Trust, and Customer satisfaction each have a significant effect on Customer loyalty among customers of PT. Sinar Sakti Sampoerna. Furthermore, these three variables simultaneously have a significant influence, demonstrating that integrated improvements in service quality, brand trust, and customer satisfaction can sustainably enhance customer loyalty